2011
DOI: 10.1002/ijc.26111
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of assay methods for detection of circulating tumor cells in metastatic breast cancer: AdnaGen AdnaTest BreastCancer Select/Detect™ versus Veridex CellSearch™ system

Abstract: The detection of CTCs prior to and during therapy is an independent and strong prognostic marker, and it is predictive of poor treatment outcome. A major challenge is that different technologies are available for isolation and characterization of CTCs in peripheral blood (PB). We compare the CellSearch system and AdnaTest BreastCancer Select/Detect, to evaluate the extent that these assays differ in their ability to detect CTCs in the PB of MBC patients. CTCs in 7.5 ml of PB were isolated and enumerated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(132 citation statements)
references
References 33 publications
8
119
0
5
Order By: Relevance
“…Recently, Markou et al described a liquid bead array hybridization assay in which mRNA isolated from immunomagnetically enriched CTCs are subjected to multiplex PCR for simultaneous measurements of the expression of 6 genes in CTCs (20 ). A commercially available RNA-based CTC assay, the AdnaTest™ (AdnaGen), uses nonquantitative RT-PCR to identify cells that express the putative transcripts of tumor-specific genes after immunomagnetic capture of MUC1 ϩ /HER2 ϩ / EpCAM ϩ cells (21 ). The assay's limitations, which derive from the fact that MUC1 is also expressed on activated T lymphocytes, should be considered (22 ).…”
Section: Mrna-based Strategiessupporting
confidence: 44%
“…Recently, Markou et al described a liquid bead array hybridization assay in which mRNA isolated from immunomagnetically enriched CTCs are subjected to multiplex PCR for simultaneous measurements of the expression of 6 genes in CTCs (20 ). A commercially available RNA-based CTC assay, the AdnaTest™ (AdnaGen), uses nonquantitative RT-PCR to identify cells that express the putative transcripts of tumor-specific genes after immunomagnetic capture of MUC1 ϩ /HER2 ϩ / EpCAM ϩ cells (21 ). The assay's limitations, which derive from the fact that MUC1 is also expressed on activated T lymphocytes, should be considered (22 ).…”
Section: Mrna-based Strategiessupporting
confidence: 44%
“…Detection of CTCs in blood is a noninvasive method of sampling and studying tumour cells compared to classic biopsy. Most CTCs enrichment methods are based on the use of EpCAM-specific antibodies and subsequent detection using anti-cytokeratin [13,14,29,30]. EpCAM is a surface marker found only on carcinoma cells.…”
Section: Discussionsupporting
confidence: 42%
“…AdnaTest used RT-PCR to detect gene transcripts of tumor markers (GA733-2, MUC-1, and HER2). The results indicated that AdnaTest has a sensitivity equivalent to that of the CellSearch system (Andreopoulou et al, 2012). Kim et al used a telomerase-specific replication-selective adenovirus to detect CTCs based on the principle that the adenovirus can replicate only in telomeraseexpressing cells and emit fluorescence in transfected cells.…”
Section: Liquid Biopsies In Tumour Diagnosis and Treatmentsupporting
confidence: 40%